Er:YAG laser application for removal of keratosis using topical anesthesia - Chang-Kai Chen; Nai-Jen Chang; Jyuhn-Hurng Ke; Earl Fu; Wan Hong Lan (Elsevier, 2013)
Fear of needle injection is one of the most common problems to affect dental procedures. The patient in this study was a 59-year-old man with contributory medical problems and smoking habits. An Er:YAG laser was used for biopsy of the right buccal tissue and tongue under topical anesthesia (Benzocaine 20%) for 1 minute without needle injection. During laser treatment, only slight bleeding occurred, eliminating the need for suturing. Histopathological examination revealed squamous cell hyperplasia without dysplasia and chronic inflammatory cell infiltration, and shrinkage and crush cells in the cutting margin. Postoperative advantages included lack of swelling, bleeding, and pain, and good wound healing.